Current use of metformin in addition to insulin in pediatric patients with type 1 diabetes mellitus: an analysis based on a large diabetes registry in Germany and Austria - Konrad, Katja; Datz, Nicolin; Engelsberger, Ilse; Grulich-Henn, Jürgen; Hoertenhuber, Thomas; Knauth, Burkhild; Meissner, Thomas; Wiegand, Susanna; Woelfle, Joachim; Holl, Reinhard W. (Pediatric diabetes, 2015)
With increasing obesity in childhood and adolescence, weight gain, and insulin resistance become also more frequent in patients with type 1 diabetes mellitus (T1DM). Especially during puberty, insulin therapy often has to be intensified and higher insulin doses are necessary. Some studies point to a beneficial effect of metformin in addition to insulin in these patients. In order to describe current practice and possible benefits, we compared pediatric T1DM patients with insulin plus metformin (n = 525) to patients with insulin therapy only (n = 57 487) in a prospective multicenter analysis.